Efficient Disproportionation of Formic Acid to Methanol Using Molecular Ruthenium Catalysts1. Issue 39 (1st August 2014) - Savourey, Solène; Lefèvre, Guillaume; Berthet, Jean‐Claude; Thuéry, Pierre; Genre, Caroline; Cantat, Thibault
Abstract The disproportionation of formic acid to methanol was unveiled in 2013 using iridium catalysts. Although attractive, this transformation suffers from very low yields; methanol was produced in less than 2 % yield, because the competitive dehydrogenation of formic acid (to CO2 and H2) is favored. We report herein the efficient and selective conversion of HCOOH to methanol in 50 % yield, utilizing ruthenium(II) phosphine complexes under mild conditions. Experimental and theoretical (DFT) results show that different convergent pathways are involved in the production of methanol, depending on the nature of the catalyst. Reaction intermediates have been isolated and fully characterized and the reaction chemistry of the resulting ruthenium complexes has been studied.